Integrating Digital Learning Media to Enhance Religious Understanding and Character Formation in Elementary Islamic Education - Nisaul Barokati Selirowangi; Muh Barid Nizarudin Wajdi; Siti Marpuah; Mohd Hisyam Bin Abdul Rahim; Mikdar Rusdi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study examines the integration of digital learning media into Islamic education at the elementary level, aiming to address the persistent gap between curriculum expectations and traditional classroom practices. The purpose of this research is to examine how digital tools enhance students’ religious understanding and character development, two critical dimensions that are often treated separately in education. A quasi-experimental design was applied, involving 120 students divided into an experimental group and a control group. The independent variable was the use of digital learning media, while the dependent variables were religious understanding and character development. Instruments included comprehension tests, teacher observation rubrics, and student engagement questionnaires. The hypothesis assumed that digital media would significantly improve both cognitive and affective outcomes. Results confirmed this assumption: the experimental group demonstrated a notable improvement in comprehension scores and showed higher levels of empathy, discipline, cooperation, and responsibility compared to the control group. The findings contribute to the discipline by presenting a holistic model that integrates multiple digital tools and by offering empirical evidence of their effectiveness. The study emphasizes the importance of integrating digital innovations into Islamic education to promote meaningful learning and character development, thereby supporting both intellectual growth and moral development among students.